Plasmid mutations affecting self-maintenance and host growth in Escherichia coli. - Koyama, A H (1975)
As reported in the accompanying paper, a number of mutants of the ColVBtrp plasmid that can not be maintained stably in the host cell of Escherichia coli have been isolated. Each of the mutated plasmids has been transferred to an isogenic Col minus strain, and the resulting Col+ strains were studied to examine the effects of plasmid mutations on some properties of the host bacteria. Many of the strains harboring a mutated plasmid were thus found to be temperature sensitive; they failed to grow and divide normally at high temperatures. Some of them formed "filaments" under these conditions. These abnormal growth characteristics were accompanied by an increased susceptibility to sodium deoxycholate and methylene blue, suggesting that the cytoplasmic membrane has been altered. Moreover, studies of temperature-independent revertants obtained from two of these temperature-sensitive Col+ strains suggested that a single mutation on the plasmid is responsible for the pleiotropic effects exerted on the host cell. The bearing of these findings on the mode of replication and segregated of stringent-type plasmids such as ColVBtrp in the host bacteria is discussed.